ANALISA USAHA KEGIATAN BUDIDAYA MINAPADIPADA KELOMPOK MINA MAKMUR DAN KELOMPOK MINA MURAKABIDI KABUPATEN SLEMAN - Elfitasari, Tita; Rejeki, Sri; Sauqie, Marâ€™I (Journal of Aquaculture Management and Technology, 2017)
Minapadi adalah budidaya pertanian dan perikanan secara terpadu bertujuan untuk meningkatkan pendapaatan, hasil, kesuburan tanah pertanian. Analisa usaha yakni suatu cara untuk mengetahui untung atau rugi dari suatu usaha. Penelitian ini dilakukan pada tanggal 29 Maret 2016 â€“ 16 April 2016.Metode yang digunakan adalah penelitian kualitatif. Tujuan dari penelitian ini adalah untuk mengetahui aspek teknis budidaya, aspek pemasaran dan aspek financial. Hasil yang didapat dari penelitian adalah Aspek sistem budidaya minapadi kelompok tani Mina Makmur dan Mina Murakabi sudah sangat bagus seperti pengeringan lahan persawahan, pembalikkan tanah persawahan, pemberian pupuk. Kelompok Mina Makmur memiliki pendapatan berkisar anatara Rp. 2.379.5790 â€“ Rp 30.997.211. Nilai NPV berkisar antara Rp. 963.659 â€“ Rp. 171.320.899, IRR berkisar antara 10% - 20%, B/C Ratio berkisar antara 0,77 â€“ 3,77 dan Payback Periode berkisar antara 0.54 â€“ 0,73. Kelompok Mina Murakabi memiliki pendapatan berkisar antara Rp. 2.438.000 â€“ Rp. 35.720.000. Nilai NPV berkisar antara Rp. 9.329.379 â€“ Rp. 112.492.353. B/C Ratio berkisar antara 1.35 â€“ 1.98 danÂ Payback Periode berkisar antara 0,52 â€“ 0,63. Dapat dikatakan kegiatan budidaya minapadi pada Mina Makmur dan Mina Murakabisangat menguntungkan dan layak untuk diteruskan. Potensi yang dimiliki oleh Mina Makmur memiliki hasil yang baik. Aspek teknis meliputi pemilihan lokasi, persiapan lahan, pemeliharaan kultivan budidaya, pemanenan, dan pemasaran tergolong baik.Rice â€“ fish â€œMINAPADIâ€ polyculture is an integrated systems between agriculture and aquaculture to increase production, revenue and fertilisation of land. The research was held 29rd March 2016 untill 16th April 2016.Â held at Business analysis is one of the method to analyse profit or loss.The purpose of this research is to observe the technological aspects, marketing aspects and financial aspect of fish farmers at Mina Makmur and Mina Murakabi.Result shows that technological aspects of minapadi system at Mina Makmurinclude draining the rice fields, the rice field soil reversal, fertilizer. Mina Makmur had revenues ranging from Rp. 2.379.5790 - Rp 30,997,211. NPV ranging between Rp. 963 659 - Rp. 171 320 899, IRR ranging from 10% - 20%, B / C ratio ranged from 0.77 to 3.77 and Payback period ranges between 0:54 - 0.73. Mina Murakabi have revenues ranging between Rp. 2.438 million - Rp. 35.72 million. NPV ranging between Rp. 9,329,379 - Rp. 112 492 353. B / C ratio ranged from 1:35 - Payback Period 1.98 and ranged from 0.52 to 0.63. Farming activities can be concluded that Mina Makmur and Mina Murakabi very profitable and feasible to be expanded. The potential Mina Makmur had good results. The technical aspects include site selection, land preparation, cultivation maintenance, harvesting, and marketing are good.Â Rice â€“ fish â€œMINAPADIâ€ polyculture is an integrated systems between agriculture and aquaculture to increase production, revenue and fertilisation of land. The research was held 29rd March 2016 untill 16th April 2016.Â held at Business analysis is one of the method to analyse profit or loss.The purpose of this research is to observe the technological aspects, marketing aspects and financial aspect of fish farmers at Mina Makmur and Mina Murakabi.Result shows that technological aspects of minapadi system at Mina Makmurinclude draining the rice fields, the rice field soil reversal, fertilizer. Mina Makmur had revenues ranging from Rp. 2.379.5790 - Rp 30,997,211. NPV ranging between Rp. 963 659 - Rp. 171 320 899, IRR ranging from 10% - 20%, B / C ratio ranged from 0.77 to 3.77 and Payback period ranges between 0:54 - 0.73. Mina Murakabi have revenues ranging between Rp. 2.438 million - Rp. 35.72 million. NPV ranging between Rp. 9,329,379 - Rp. 112 492 353. B / C ratio ranged from 1:35 - Payback Period 1.98 and ranged from 0.52 to 0.63. Farming activities can be concluded that Mina Makmur and Mina Murakabi very profitable and feasible to be expanded. The potential Mina Makmur had good results. The technical aspects include site selection, land preparation, cultivation maintenance, harvesting, and marketing are good.